Spectrum of nonlinear magnetoelastic waves in a cubic ferromagnet - Vakhitov, R.M.; Ryakhova, O.G. (Functional Materials, 2004)
Peculiarities of the nonlinear magnetoelastic (ME) wave spectrum in a cubic ferromagnet with induced uniaxial anisotropy along [111] have been studied theoretically. It has been shown that in the case of resonance, as the wave attains a certain velocity in the magnet along the [111] axis, a possibility appears for a movement of the 60-degree domain wall without magnetization deviation from the spin rotation plane. The presence of ME interaction has been found to result in a violation of conditions for that resonance type appearance and to give rise to new solutions. Теоретически исследуются особенности спектра нелинейных магнитоупругих (МУ) волн в кубическом ферромагнетике с наведенной вдоль [111] одноосной анизотропией. Показано, что в резонансном случае при достижении волной определенной скорости в магнетике вдоль оси [111] возможно движение 60-градусной доменной границы без выхода намагниченности из плоскости вращения спинов. Установлено, что наличие МУ взаимодействия приводит к нарушению условий возникновения такого типа резонанса и появлению новых решений. Теоретично досліджуються особливості спектрa нелінійних магнітопружних хвиль у кубічному феромагнетику з наведеною вздовж [111] одновісною анізотропією. Показано, що у випадку резонансу при досягненні хвилею певної швидкості в магнетику вздовж осі [111] можливий рух 60-градусної доменної межі без виходу намагніченості з площини обертання спінів. Встановлено, що наявність магнітопружної взаємодії призводить до порушення умов виникнення такого типу резонансу та до появи нових рішень.